Reproductive success of nuclear nonhybrid males of Squalius alburnoides hybridogenetic complex (Teleostei, Cyprinidae): An example of interplay between female choice and ecological pressures? - Santos, Carla Sousa (2012)
The hybridogenetic fish complex Squalius alburnoides comprises diploid males with non-hybrid nuclear genomes and several hybrid forms varying in ploidy and relative proportions of the parental genomes. In this paper, we present evidence that in captivity females prefer to mate with non-hybrid males. We suggest that female choice combined with different ecological requirements of hybrid and non-hybrid males may explain the extreme variation in the relative abundance of male types among drainages.